Eksplorasi Geometri Bangun Ruang Wisata Religi Mandala Giri di Gunung Srandil - Faozan, Dani; Kusno, Kusno (Universitas Negeri Surabaya, 2024)
This research aims to explore the spatial geometry found in the Mandala Giri religious tourism building on Mount Srandil. The research method used in this research is qualitative with an ethnographic approach. Data analysis techniques were carried out using data reduction, as well as draweing conclusions and verification based on the Miles and Huberman method. The results of this research found the concept of flat shapes with flat sides, namely rectangular pyramids, octagonal prisms, cubes, and blocks. The shape of the curved side room is also found in monastery buildings, namely in the form of a tube, and there is a combination of hexagonal prisms and pyramid room structures. This research shows that the culture in Indonesia can be used as material for learning mathematics.